Air Pollution Emergency and Human Health Crisis – Doable Risk Reduction Strategies - Dyriam, Helen Christina; Panneer, Sigamani; Christy, Jayakumar (Indian Journal of Community Health, 2024)
Background: The environmental devastation wrought by indoor and ambient air pollution is causing immeasurable stress and strain on the health of people and projected to increase mortality and morbidity rate specifically due to accumulation of particulate matter and ground-level ozone in the atmosphere. Objective: This work aims to provide a comprehensive outlook on the global death and disease burden, impact on low- and middle-income countries’ population with focus on Asian countries, health vulnerability and projected hazards of particulate air pollution. Methods: Data pertaining to air pollution and health impacts were collected from web sources following PRISMA model, analysed and interpreted. Results: The authors found that the ominous environmental magnification and accumulation of air pollutants is the greatest threat questioning human existence in the near century. Conclusion: The interdependent augmentation of global warming and air pollution is further worsening climatic conditions and disease occurrence. Hence this work recommends evidence-based policy framework and synergistic actions to allay air pollutants thereby enhancing eco-survival.